2010
DOI: 10.17763/haer.80.2.hw3483147u83684h
|View full text |Cite
|
Sign up to set email alerts
|

"The Beauty of America": Nationalism, Education, and the War on Terror

Abstract: In this article, Thea Renda Abu El-Haj draws on qualitative research conducted with Palestinian American high school students to explore school as a key site for nation building. By focusing on their teachers' talk and practice, she examines how U.S. nationalism and national identities are produced through everyday racialized and gendered discourses and practices inside one school. She argues that this nation building is deeply entwined with the cultural logic that undergirds U.S. imperial ambitions in relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Through immersive observation and interviews with Muslim American students at a public high school in Pennsylvania, Abu El-Haj (2010), for instance, describes the systematic alienation of Muslim American students from the democratic discourse. Abu El-Haj (2010) found that administrators and teachers tended to describe Muslim American students as inherently oppositional to three recurring democratic values-freedom, tolerance, and liberty. These perceptions positioned Muslim American students outside of the democratic discourse, decreasing their acceptance and ability to self-identify as Americans.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through immersive observation and interviews with Muslim American students at a public high school in Pennsylvania, Abu El-Haj (2010), for instance, describes the systematic alienation of Muslim American students from the democratic discourse. Abu El-Haj (2010) found that administrators and teachers tended to describe Muslim American students as inherently oppositional to three recurring democratic values-freedom, tolerance, and liberty. These perceptions positioned Muslim American students outside of the democratic discourse, decreasing their acceptance and ability to self-identify as Americans.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this chapter, we also expand the frameworks within which youths’ lives have been understood to include imperial power (Abu El-Haj, 2010; Maira, 2009). It is beyond the scope of this chapter to discuss the extensive debates about imperialism.…”
Section: Understanding the Impact Of Globalization Nationalism And mentioning
confidence: 99%
“…For our purposes, we are referencing the ways that the United States and European nations have exercised and continue to exercise military, economic, and political power on a global stage (see Justice, 2010; Khalidi, 2004; Maira, 2009; Mamdani, 2004). There has been little literature that uses imperialism as a framework for understanding the education of youth from Muslim transnational communities in today’s schools (see, for exceptions, Abu El-Haj, 2010; Maira, 2009). Imperialism must be considered in relation to both state policies (power and authority) and the cultural discourses that justify, and thus are intimately intertwined with, these state policies.…”
Section: Understanding the Impact Of Globalization Nationalism And mentioning
confidence: 99%
See 1 more Smart Citation
“…In Florida, 145 anti‐Muslim bias incidents of targeted harassment were reported (Council on American‐Islamic Relations, ). Because of the diversity in BCPS, it is important to understand that such students can be viewed as potentially violent simply because they are seen as foreign (El Haj & Renda, ). In 2015, the Federal Bureau of Investigation (FBI) reported that 21.9% of hate crimes during that year were of an anti‐Muslim basis (FBI, ).…”
Section: Introductionmentioning
confidence: 99%